2007
DOI: 10.1387/ijdb.072365lf
|View full text |Cite
|
Sign up to set email alerts
|

Mouse models to study inner ear development and hereditary hearing loss

Abstract: Hereditary sensorineural hearing loss, derived from inner ear defects, is the most common hereditary disability with a prevalence of 1 in 1000 children, although it can be present in up to 15% of births in isolated communities. The mouse serves as an ideal animal model to identify new deafness-related genes and to study their roles in vivo. This review describes mouse models for genes that have been linked with hearing impairment (HI) in humans. Mutations in several groups of genes have been linked with HI in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
84
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(88 citation statements)
references
References 247 publications
(207 reference statements)
0
84
0
Order By: Relevance
“…Several genes essential for hearing in humans were identified after they had already been demonstrated to be associated with deafness in mice. 8 Using homozygosity mapping and candidate gene analysis, we identified a homozygous nonsense mutation in CLIC5 in a consanguineous Turkish family (W05-009). The orthologous mouse gene, Clic5, was described to be mutated in the jitterbug (jbg) mouse exhibiting congenital progressive hearing impairment and vestibular dysfunction due to progressive hair cell degeneration.…”
Section: Introductionmentioning
confidence: 99%
“…Several genes essential for hearing in humans were identified after they had already been demonstrated to be associated with deafness in mice. 8 Using homozygosity mapping and candidate gene analysis, we identified a homozygous nonsense mutation in CLIC5 in a consanguineous Turkish family (W05-009). The orthologous mouse gene, Clic5, was described to be mutated in the jitterbug (jbg) mouse exhibiting congenital progressive hearing impairment and vestibular dysfunction due to progressive hair cell degeneration.…”
Section: Introductionmentioning
confidence: 99%
“…Auditory mouse mutants have contributed to the identification of candidate deafness-causing genes in humans [6,10,11]. Due to the remarkable structural similarity between human and mouse auditory systems, auditory mouse mutants have provided valuable insight into the ontogenesis, morphogenesis and function of the human ear [3].…”
Section: Introductionmentioning
confidence: 99%
“…Vertebrate inner ear hair cells are mechanosensors that transduce mechanical forces arising from sound waves and head movement providing the sense of hearing and balance, respectively [13,23]. Stereocilia is a mechanically sensitive organelle, which consists of actin filaments, nonmuscle-type myosin and several scaffold proteins [6,10,11]. Mouse mutations underlying vestibular dysfunction and deafness occur preferentially in genes encoding such proteins.…”
Section: Introductionmentioning
confidence: 99%
“…The molecular mechanisms governing the ankle link and the basal link assemblies are not well characterized, but there is evidence showing several USH gene products including cadherin 23, VlgR, and Usherin are crucial for their formation (8)(9)(10). Studies using the animal models of USH showed that mutation of any one of the Usher genes affects the development of stereocilia at different degrees (11)(12)(13)(14).…”
mentioning
confidence: 99%